Astrocyte‐like glial cells physiologically regulate olfactory processing through the modification of ORN‐PN synaptic strength in Drosophila. (26th June 2014) - Liu, He; Zhou, Bangyu; Yan, Wenjun; Lei, Zhengchang; Zhao, Xiaoliang; Zhang, Ke; Guo, Aike
Abstract Astrocyte‐like glial cells are abundant in the central nervous system of adult Drosophila and exhibit morphology similar to astrocytes of mammals. Previous evidence has shown that astrocyte‐like glial cells are strongly associated with synapses in the antennal lobe (AL), the first relay of the olfactory system, where olfactory receptor neurons (ORNs) transmit information into projection neurons (PNs). However, the function of astrocyte‐like glia in the AL remains obscure. In this study, using in vivo calcium imaging, we found that astrocyte‐like glial cells exhibited spontaneous microdomain calcium elevations. Using simultaneous manipulation of glial activity and monitoring of neuronal function, we found that the astrocyte‐like glial activation, but not ensheathing glial activation, could inhibit odor‐evoked responses of PNs. Ensheathing glial cells are another subtype of glia, and are of functional importance in the AL. Electrophysiological experiments indicated that astrocyte‐like glial activation decreased the amplitude and slope of excitatory postsynaptic potentials evoked through electrical stimulation of the antennal nerve. These results suggest that astrocyte‐like glial cells may regulate olfactory processing through negative regulation of ORN–PN synaptic strength. Beyond the antennal lobe we observed astrocyte‐like glial spontaneous calcium activities in the ventromedial protocerebrum, indicating that astrocyte‐like glial spontaneous calcium elevations might be general in the adult fly brain. Overall, our study demonstrates a new function for astrocyte‐like glial cells in the physiological modulation of olfactory information transmission, possibly through regulating ORN–PN synapse strength.